2019
DOI: 10.1139/apnm-2018-0265
|View full text |Cite
|
Sign up to set email alerts
|

Pulse wave reflection responses to bench press with and without practical blood flow restriction

Abstract: Acute bench press resistance exercise using LL-pBFR or HL, significantly altered pulse wave reflection characteristics without differences between LL-pBFR and HL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 48 publications
8
25
0
Order By: Relevance
“…The Cochrane Collaboration's tool for assessing risk could only be used for four studies, 19‐22 as the other included study did not utilize a randomized design 23 . The review authors’ judgments about each risk of bias are shown in Figure 2 as percentages across all included studies and detailed in Figure 3 for each study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Cochrane Collaboration's tool for assessing risk could only be used for four studies, 19‐22 as the other included study did not utilize a randomized design 23 . The review authors’ judgments about each risk of bias are shown in Figure 2 as percentages across all included studies and detailed in Figure 3 for each study.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Tai et al 23 compared the acute effects of post‐exercise central hemodynamics between bench press exercise performed at 30% 1RM with LIRE‐BFR and high‐intensity resistance exercise at 70% 1RM. Their results showed that LIRE‐BFR bench press exercise acutely increased AP, AIx, and AIx75 parameters in resistance‐trained men similarly to high‐intensity resistance exercise.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations